Sports psychology in Brazil: Review in psychology journals - Brandt R.* (2015)
The aim of this study was to systematically review the literature issues on sports psychology in journals of psychology. Electronic search in SciELO (Human Science area) and PePSIC databases was performed. As descriptors, the terms Sports Psychologist, sport, and athletes were used. For the selection it was not established period of time. Among the 84 index journals in Human Science in the SciELO database, 14 journals took part in the sample. In the PePSIC database 66 journals were found and 8 were included in the study. Altogether, 66 articles were selected. However after meeting the inclusion criteria only 39 were analyzed. The findings showed that despite the increase of production in the area between 2010 and 2012 very little is produced on the sports psychology. Understanding the scientific production of sports psychology in journals of psychology enables tracing the profile of the published studies, identifying future directions to the area.